Polska i Białoruś - trudne sąsiedztwo. Polityka "krytycznego dialogu" wobec autorytarnej Białorusi - Fedorowicz, Krzysztof (Wydawnictwo Naukowe Wydziału Nauk Politycznych I Dziennikarstwa UAM w Poznaniu, 2012)
For over ten years Polish-Belarusian political relations have been characterized by a lack of opportunities for real collaboration, caused by the non-democratic nature of the Belarusian political system. The international isolation of its authoritarian regime also influences bilateral relations. In the period from 1996–2008 Poland adopted a principle of critical dialogue in its policy towards Belarus. This implied official criticism of the infringement of human rights and breaking of democratic rules while refraining from a total abandonment of dialogue with the Belarusian authorities, although the level and intensity of this dialogue was significantly diminished. It was assumed that the complete isolation of the Belarusian authorities was not in Polish interests and preferential treatment would help to ensure the fundamental rights of the Polish minority in Belarus. This policy turned out to be ineffective, though, in relation to a state that does not acknowledge the basic principles and laws of international relations. To a large extent, the specific character of the Belarusian political system has been, and will remain, the greatest obstacle in the further development of Polish-Belarusian relations, and will significantly restrict the possibility of building good relations in the future.
Poland and Belarus – difficult neighborhood. A policy of ‘critical dialogue’ towards authoritarian Belarus
Keywords: Białoruś; polityka zagraniczna; Belarus